(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This study is targeted at the synthesis of a new imine-chelator and its Fe2+, Ni2+ and Cu2+ chelates derived from 2-hydroxyl-1-naphthaldehyde and 2-amino-4-methylphenol for characterization and; for bactericidal, anti- fungiform, antioxidant and extractive potentials’ evaluations.Spectral (UV/visible, vibrational, plus nuclear magnetic resonance) methods, analytical (C, H, N, Melting point, magnetic susceptibility, and conductance, complexometric) techniques and biological (antimicrobial, antioxidant plus extractive potentials) appraisals were all adopted for the study of the synthesized chelator and its chelates. A new-fangled heterocyclic chelator, 3-[(2-hydroxy-5-methylphenylimino)-methyl]-napthalen-2-ol and its Fe2+, Ni2+ and Cu2+ chelates were synthesized and characterized with proton nuclear magnetic resonance (1H NMR), vibrational (FT-IR), mass (ESI-MS) and electronic spectral techniques; in addition to micro (C,H,N)analysis, magnetic susceptibility (µeff), plus molar conductance evaluations. The acquired FT-IR spectral values denoted excellent chelation attributes of the chelator towards the 3d-M2+ ions through the deprotonated oxygenand imine nitrogen atoms. The structural assemblages leading to the geometries (octahedral, square planar plus tetrahedral for Fe2+, Cu2+ and Ni2+ chelates) were deduced from experimental data arising from C,H,N-analysis, µeff , plus electronic spectral evaluations. In addition to the latter, the 1H NMR plus ESI-MS values provided the basis for the proposed structure of the chelator. Molar conductance data validated the neutrality of the chelates. The acquired ESI-MS spectrum presented convincing fragmentation pathways, stoichiometric contents, as well as formula weight for the chelator. The in vitro antimicrobial actions of the compounds against isolated microbial strains exhibited altered actions. The [Fe(C36H32N2O6)] demonstrated superlative antimicrobial actions against all the tested microbes with inhibitory growth zones comparable to that of the adopted standard drugs. The compounds presented excellent DPPH antioxidant scavenging actions, with the [Ni(C36H30N2O5)] chelate having the most outstanding antioxidant action with an IC50 of 98%, IC100 of 99% and IC200 of 99% compared to others.